Kejadian Stunting dengan Perkembangan Motorik Halus Pada Balita - Vania Petrina Calista; T A Larasati; Wuryaningsih Dwi Sayekti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: stunting is a physical growth disorder in children which is characterized by short stature and is characterized by impaired brain development. Purpose: determine the relationship between the incidence of stunting with motor development in toddlers. Methods: This research is an analytic observational with a cross sectional approach. The research was conducted in July 2021 in Jatimulyo Village, Jati Agung District, South Lampung. Sampling with a total sampling of 50 toddlers. Data collection tools using questionnaires and observation sheets. Data analysis used percentage and Chi-Square test. Results: Most of the toddlers were not stunted and had fine motor development that was appropriate for their age. There is a significant relationship between the incidence of stunting and fine motor development in toddlers. The community can pay more attention to parenting patterns and the provision of nutritious food so that it can reduce child mortality due to stunting as well as a reference for designing health programs in order to improve the health status of toddlers.